GAMBARAN TINGKAT SELF- REGULATED LEARNING PADA SISWA SEKOLAH DASAR - Fadilah Fitria Harahap; Nurwahyuni Nasir; Lenny Utama Afriyenti (ADIBA : JOURNAL OF EDUCATION, 2025)
Self-regulated learning (SRL) is an important ability in the student learning process to manage thoughts, motivations, and behaviors independently in achieving goals. The ability of students to regulate themselves in learning from an early age is important to form learning independence, academic achievement, and readiness to face the challenges of the 21st century. This study aims to find out the overview of the level of self-regulated learning in elementary school students. The research method used in this study is a descriptive quantitative method. The respondents of this study are active students in grade 5 of elementary school. The sampling technique used a total sampling with 125 students. This research instrument was prepared based on aspects from Zimmerman (1990), namely metacognitive, motivational, and behavioral. The results of the categorization test showed that the majority of students (72.8%) had SRL levels in the low category, 16% in the high category, and 11.2% in the low category. The difference test showed that there was a significant difference in SRL by gender, where female students had higher levels of SRL than male students. However, no significant differences were found by class or age.